Internet-based monitoring and controlling of real-time dynamic systems - Al Shoaili, Saoud Humaid Salim (Curtin University, 2005)
The study in this report mainly focuses on the Internet-based Monitoring and Controlling of a Real-Time Dynamic System interfaced via a dedicated local computer. The main philosophy behind this study is to allow the remote user to conduct an Internet-based Remote Operation (I-bRO) for the dynamic system. The dynamic system has been defined as the system which has its parts interrelated in such a way that a change in one part necessarily affects other parts of the system [I]. In order to achieve this goal, the study has been conducted in a form of an on-line and real-time Virtual Laboratory (VL). Through this form of laboratory, a user can carry out the experiment, perform real-time monitoring and controlling operations of the experiment and collect real and live data from the experiment through the network link as the user was physically in the laboratory. The dynamic system that has been selected for the test-rig of this study is a 3-phase Induction Motor (IM) which is mechanically coupled with a DC-Dynamometer that acts as a variable load to the IM. This system is a common laboratory experiment in the study of the Electrical Engineering for both undergraduate and postgraduate students. The study covers both sides of the I-bRO; the hardware and the software. The hardware side includes the design and the development of a load control box that has been used to interface the DC-Dynamometer and consequently control it from the local computer. The software side covers the design and the development of the Virtual Instrumentation System (VIS) that has replaced successfully the physical Measurement and Test (M&T) instruments of the test-rig. Beside that, the software side includes the development of the internet remote front panel for the remote operation.Furthermore, the software side includes the development of the software that has been used to analyse the system during the I-bRO. In this study, the LabVTEW7 program has been used to design and develop the VIS and the Matlab program has bee used to aualyse the system performance for the remote operations. This study also addresses the issues and problems related to the intranet or the internet to be used as the network for data communication between the test-rig and remote users. This study has been carried out in different stages as follows: 1. Designing and development of the VIS. 2. Interfacing the test-rig apparatus with a local computer. 3. Upload the system from the local computer to the network. 4. Study the performance of the system on the network for the purpose of the remote operations controlled over the internet. The developed system of this study has been used for data acquisition, network communications, instruments monitoring and controlling applications. A user can execute on-line and in the real-time the developed VIS from any point in the university. Due to the fact that the university network is directly integrated to the main internet server. a remote user through the main internet server is able to perform I-bRO of the selected dynamic system. There are many factors associated with the network, the internet or the intranet, and have direct influences on the control system performance throughout the remote operations. The most dominant factors are the random time-delays and the data losses.These factors among others have to be addressed for a proper application of the I-bRO. For this reason, different cases and scenarios of the I-bRO have been investigated and simulated to study the affection of the network on the control system performance. The system is analysed under two control cases, closed loop with random time-delays and open loop when the internet server is disconnected and no communication between the input and the output of the system. In the first case, the closed loop, the internet server is assumed to be closed and subjected to random time-delays. In the second case, the internet server is subjected to random cut-off and thus opens the control loop. The results of both cases have been analysed and discussed. It has been found that, if the control system without the time-delays is stable, it remains stable even with small time-delays up to twenty seconds. This result is different from what has been shown in the literature.